2020
DOI: 10.1242/dmm.044990
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed nitric oxide signalling gives rise to congenital bicuspid aortic valve and aortopathy

Abstract: Patients with a congenital bicuspid aortic valve (BAV), a valve with two instead of three aortic leaflets, have an increased risk of developing thoracic aneurysms and aortic dissection. The mechanisms underlying BAV-associated aortopathy are poorly understood. This study examined BAV-associated aortopathy in Nos3−/− mice, a model with congenital BAV formation. A combination of histological examination and in-vivo ultrasound imaging was used to investigate aortic dilation and dissections in Nos3−/− mice. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 55 publications
1
16
1
Order By: Relevance
“…In view of the human fragile aortic wall it is probably this third/noncoronary valve leaflet's etiology that associates with the differentiation of the outer media of the aortic wall, and that becomes prone to aneurysm formation. The inner media of the wall of the ascending aorta is NC derived [41,57], whereas the outer media/adventita is SHF derived [5,36]. We postulate that anomalous SHF differentiation may affect both this semilunar valve leaflet and the integrity of the ascending aorta.…”
Section: Bicuspid Semilunar Valvesmentioning
confidence: 86%
“…In view of the human fragile aortic wall it is probably this third/noncoronary valve leaflet's etiology that associates with the differentiation of the outer media of the aortic wall, and that becomes prone to aneurysm formation. The inner media of the wall of the ascending aorta is NC derived [41,57], whereas the outer media/adventita is SHF derived [5,36]. We postulate that anomalous SHF differentiation may affect both this semilunar valve leaflet and the integrity of the ascending aorta.…”
Section: Bicuspid Semilunar Valvesmentioning
confidence: 86%
“…Adriana C. Gittenberger-de Groot and her team have performed an extensive number of indispensable studies on the spectrum of BAV disease and associated aortic anomalies over the past three decades. This contribution includes several developmental, histopathological, and anatomical studies on animal as well as human tissue, such as the meticulous explanation of cardiac development in congenital malformations [ 10 ], anatomical description of BAV and the aortic root [ 11 ], and the contribution of several cell lineages to the development of BAV and the associated aortic root anomalies [ 12 , 13 , 14 ]. In addition, other groups have reported that patient-specific factors such as aortic valve stenosis (AS), in combination with the specific leaflet morphology (the type of BAV) and the resultant shear stress, were associated with dilatation of the aorta [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Peterson et al used a mouse model deficient in NO synthase 3 ( Nos3 −/− ), essential for the balance of NO, which present congenital BAV. These mice developed dissections in the ascending aorta as a result of changes in NO signaling that disturb the profile of elastin [ 81 ]. Another study, carried out by Gauer et al, showed that in non-dilated ascending aorta wall from BAV patients, there were lower levels of NOS3 than in those with TAV.…”
Section: Molecular and Cellular Biology Of The Aortic Valve And Associated Aortopathymentioning
confidence: 99%